Spanish Civil War - National Council of Labour Appeal, 1937 (1937)
1937 1918-1939 "Spanish Civil War - National Council of Labour Appeal, 1937" [T0145.jpg], 1937, Labour Party The National Council of Labour, Comprising the Labour Party and the Trades Union Congress, established its fund for Spain in 1936. Some unions organised levies of their membership and the miners alone contributed £70.000. By the end of the war, the British Labour Movement had contributed £200,000 worth of supplies to the Republican side. The funds were used for humanitarian relief only and were channelled through the International Solidarity Fund established by the International Federation of Trade Unions and the Labour and Socialist International in 1934 to support victims of fascism.